2010
DOI: 10.1111/j.1365-2966.2009.15794.x
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the effect of active galactic nuclei feedback on the metal enrichment of galaxy clusters

Abstract: We present a study of the effect of active galactic nuclei (AGN) feedback on metal enrichment and thermal properties of the intracluster medium (ICM) in hydrodynamical simulations of galaxy clusters. The simulations are performed using a version of the TreePM–sphgadget‐2 code, which also follows chemodynamical evolution by accounting for metal enrichment contributed by different stellar populations. We carry out cosmological simulations for a set of galaxy clusters, covering the mass range M200≃ (0.1–2.2) × 10… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

49
312
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(361 citation statements)
references
References 122 publications
(312 reference statements)
49
312
0
Order By: Relevance
“…Roediger et al (2007) studied the effect of bubble-induced motions on metallicity profiles through 3D hydro simulations. The new simulation by Fabjan et al (2010) showed a less steep central Fe peak including feedback from AGN in cD galaxies. The observed small scatter in the Fe abundance slope within 0.1r 180 in the cD clusters suggests a common process of metal supply and ejection in the cD galaxies.…”
Section: Fe Profiles Within the Cool Core Regionsmentioning
confidence: 81%
“…Roediger et al (2007) studied the effect of bubble-induced motions on metallicity profiles through 3D hydro simulations. The new simulation by Fabjan et al (2010) showed a less steep central Fe peak including feedback from AGN in cD galaxies. The observed small scatter in the Fe abundance slope within 0.1r 180 in the cD clusters suggests a common process of metal supply and ejection in the cD galaxies.…”
Section: Fe Profiles Within the Cool Core Regionsmentioning
confidence: 81%
“…These measures represent the "footprint" of cosmic star formation history and are crucial to tracing the effect of SN feedback on the ICM at different cosmic epochs (e.g. Ettori 2005;Calura et al 2007;Cora et al 2008;Fabjan et al 2010). …”
Section: Introductionmentioning
confidence: 99%
“…The main argument in favour of this mode is that the AGN activity is directly tied to the state of the diffuse gas because the Bondi accretion rate depends on the gas density and temperature in the vicinity of the black hole (Allen et al 2006). For this reason, this is the fueling mode most commonly invoked in cosmological simulations of galaxies, galaxy groups and clusters of galaxies (e.g., Di Matteo, Springel & Hernquist 2005;Fabjan et al 2010;Dubois et al 2011;Bellovary et al 2013;Le Brun et al 2014). However, a detailed analysis of AGN activity in galaxy clusters (Rafferty et al 2006;McNamara, Rohanizadegan & Nulsen 2011) indicates that the hot-mode accretion is much too small (by orders of magnitude) to account for the observed outbursts (but see Fujita, Kawakatu & Shlosman 2014).…”
Section: Introductionmentioning
confidence: 99%